Pyla-Kokkinokremos, Maa-Palaeokastro and the settlement histories of Cyprus in the twelfth century BC - Georgiou, A; Artemis Georgiou (2012)
The present thesis provides a methodological examination of Pyla-Kokkinokremos and Maa-Palaeokastro, two settlement-sites that were established in Cyprus during the transition from the Late Cypriot IIC (roughly the thirteenth century BC) to the Late Cypriot IIIA (roughly the twelfth century BC). These two settlements were extremely short-lived and persisted for merely a couple of generations before their eventual abandonment. The period under consideration is often referred to as the “Crisis Years”, and marks a time when the politically and economically powerful land-based polities of the eastern Mediterranean were brought to an end. The foundation of Pyla-Kokkinokremos and Maa-Palaeokastro coincides with these critical years for the eastern Mediterranean and the upheaval of the settlement pattern of Cyprus. Since their excavation, the two sites have been considered as two very controversial and intriguing phenomena. Their selected position on top of naturally fortified locations and the marked absence of perennial water sources in their vicinity suggested that they were established in order to fulfil a special purpose. The original suggestion put forward by the excavator that Pyla-Kokkinokremos and Maa-Palaeokastro represent the earliest establishments of refugees fleeing from the Aegean following the palatial collapse has been questioned by a number of scholars, who insist on the Cypriot character of the two sites, and therefore consider them as outposts established by local populations. This dissertation provides a re-examination of the topographical setting of the two settlements, their architectural characteristics and their material culture, mostly pottery, aiming to determine the series of events that led to their establishment, as well as the roles and functions fulfilled by the two sites. The objective of this study is not exclusively concerned with the detailed presentation of excavated architectural and artefactual remains from Pyla-Kokkinokremos and Maa-Palaeokastro. In extent, the aims of this thesis are to define the character of Cyprus during the years marking the transition from the thirteenth to the twelfth century BC, and examine transformations in the settlement pattern of the island, its socio-political landscape and provide a holistic approach of its material culture.